Improving the Quality of Two Lives by Treating Obesity - Norbert Nagy; Patrícia Kleinová; Martin Jozef Péč; Matej Samoš; Ivana Dedinská (Reports)
Background and Clinical Significance: Kidney transplantation remains the most effective method of renal replacement therapy. Living donor transplantation offers several advantages—reduced cardiovascular risk, better graft survival, and preemptive intervention. However, donor obesity is a growing concern, as it is usually associated with perioperative and long-term complications, which can affect donor eligibility. Bariatric surgery is a standard recommendation for patients with a BMI over 35 kg/m2. There are limited data on the use of pharmacological agents for weight reduction in kidney donors. This case presents a successful conservative treatment with GLP-1 receptor agonist in an obese woman wishing to donate a kidney to her son. Case Presentation: We are presenting the case of a 63-year-old woman with grade II obesity who was initially denied being a kidney donor to her son because of her weight. Under these circumstances, she underwent comprehensive lifestyle modification in the cardio-obesitology clinic (caloric restriction, physical activity, and pharmacological treatment with liraglutide). During the 3-month follow-up, she decreased her BMI to 33.4 kg/m2, and subsequent examinations confirmed no surgical contraindications to donating a kidney. Despite hematuria, biopsy and genetic testing revealed a benign carrier condition of Alport syndrome, which, without proteinuria or renal impairment, allowed successful kidney donation. Conclusions: This case demonstrates that conservative pharmacological treatment for body weight reduction with GLP-1 receptor agonists may be an alternative to bariatric surgery for selected obese kidney donor candidates. The presented case highlights the importance of a multidisciplinary and personalized approach.